TRAINING OF COVID-19 VOLUNTEER - Irisanna Tambunan; Angga Satria Pratama; Tri Nur Jayanti; Anri Anri; Sri Ayu Arianti (JCES (Journal of Character Education Society), 2021)
Abstrak: Rukun Warga (RW) 14 Bumi Harapan merupakan salah satu bagian wilayah di Kecamatan Cibiru Hilir yang berdekatan dengan pasar induk Gede Bage sebagai zona rawan penyebaran COVID-19, berisiko penularan dari blok lain yang telah terdapat kasus terkonfirmasi COVID-19. Tim Relawan Covid-19 tingkat RW belum pernah dibentuk sehingga  pemahaman dan keterampilan masyarakat menghadapi temuan kasus COVID-19 kurang adekuat. Keterbatasan pengetahuan dan keterampilan terkait COVID-19 menyebabkan kepanikan masyarakat, sehingga pelatihan relawan COVID-19 sebagai langkah untuk meningkatkan pengetahuan dan keterampilan dalam menyikapi temuan kasus COVID-19 sehingga masyarakat siap siaga. Kegiatan ini melibatkan perangkat RW, RT, tokoh masyarakat, kader secara sukarela bersiapsiaga dalam menghadapi COVID-19. Pelatihan dilakukan selama 3 jam dengan metode ceramah, demonstrasi, diskusi; pembentukan dan pelatihan relawan tanggap COVID-19; evaluasi dan monitoring pelaksanaan protokol kesehatan pencegahan COVID-19 dan peran tim relawan di masyarakat. Media powerpoint, video, modul pelatihan digunakan untuk memudahkan sasaran menerima informasi. Evaluasi dilakukan saat pelatihan dan 1 bulan setelah pelatihan untuk mengetahui keberhasilan dan memantau keberlangsungan program setelah pelatihan selesai diberikan. Hasil kegiatan ini yaitu terlaksananya pelatihan yang dihadiri oleh 17 peserta. Seluruh peserta dapat mengikuti acara sampai selesai dengan kondusif dan dapat menerima materi dengan baik berdasarkan hasil pengisian kuesioner saat post test sebagian besar berpengetahuan baik.Abstract: Rukun Warga (RW) 14 Bumi Harapan is a part of the area in Cibiru Hilir District which is close to the Gede Bage main market as a zone prone to the spread of COVID-19., RW 14 is in the BB Bumi Harapan block that is at risk of experiencing COVID-19 transmission from other blocks where there have been confirmed cases of COVID-19. The Bandung District Health Office previously sent a task force team to handle COVID-19 at the start of the COVID-19 pandemic. However, the departure of the task force team did not leave the understanding and skills of the local community in dealing with the findings of the COVID-19 case while the COVID-19 pandemic is still continuing to this day. The limited knowledge and skills of the community related to COVID-19 caused panic in the local community. Therefore, training for COVID-19 volunteers at the RW is deemed necessary as a step to increase knowledge and skills in responding to the findings of the COVID-19 case so that the public is prepared to be alert when a COVID-19 case is found. This activity involves RW units, community leaders, cadres, and local communities who voluntarily prepare to face COVID-19. The training was held for 3 hours using lectures, demonstrations, and discussion / question and answer methods; formation and training of COVID-19 response volunteers; evaluating and monitoring the implementation of the COVID-19 prevention health protocol and the role of volunteer teams in the community. Powerpoint media, videos, and training modules are used to make it easier for targets to receive the information provided. Evaluation is carried out immediately after training and 1 month after training to determine the success of the training and to monitor the continuity of the program after the training has been completed. The result of this activity was the implementation of the training which was attended by 16 participants well. All participants can participate in the event until it ends in a conducive way. All participants were also able to receive the material well based on the results of filling out the questionnaire during the post-test which the average score was 80. This activity also received a positive response based on the participants' responses during the activity. Keywords: Health education, skills improvement, orphanages.